Business Process Improvement Melalui Penambahan Alat Bantu Oil Drain Pada PT Komatsu Indonesia - Sumasto, Fredy; Agus, Muhamad; Salam, Suriadi A.; Fathullah, Abi Sufyan (Journal of Community Services in Sustainability, 2024)
This article outlines the results of the Community Service, which aims to improve business processes at PT Komatsu Indonesia by adding oil drain tools. The main problem identified was wasting time and resources in draining waste oil from testing components in the Hydraulic Tester Machine (HTM). To solve this problem, we designed and implemented a tool in the form of an oil pump hose jig that is integrated directly into the reservoir. As a result, draining waste oil can be done more efficiently and safely, reducing the potential waste of time and the risk of work accidents. In addition, suggestions for further development include improving the tool's design by paying attention to ergonomic and biomechanical aspects and reliability tests to determine the life and reliability of the tool. Hopefully, implementing this tool can provide more optimal benefits in improving the efficiency of business processes and the welfare of workers at PT Komatsu Indonesia. Artikel ini menguraikan hasil dari Pengabdian kepada Masyarakat (PkM) yang bertujuan untuk meningkatkan proses bisnis di PT Komatsu Indonesia melalui penambahan alat bantu oil drain. Masalah utama yang diidentifikasi adalah pemborosan waktu dan sumber daya dalam proses pengurasan limbah oli hasil pengujian komponen-komponen di Hydraulic Tester Machine (HTM). Untuk mengatasi masalah ini, kami merancang dan mengimplementasikan alat bantu berupa jig hose oil pump yang terintegrasi langsung di dalam bak penampungan. Hasilnya, proses pengurasan limbah oli dapat dilakukan secara lebih efisien dan aman, mengurangi potensi pemborosan waktu dan risiko kecelakaan kerja. Selain itu, saran untuk pengembangan selanjutnya termasuk peningkatan desain alat bantu dengan memperhatikan aspek ergonomis dan biomekanika serta realibility test untuk mengetahui umur dan keandalan alat bantu. Diharapkan, implementasi alat bantu ini dapat memberikan manfaat yang lebih optimal dalam meningkatkan efisiensi proses bisnis dan kesejahteraan pekerja di PT Komatsu Indonesia.